Predictors of Perceived Social Support, Quality of Life, and Resilience in Pregnancy - Jafaru, Yahaya; Murtala Musa, Muhammed; Wasagu Sani, Gaddafi (Alta Dharma Publisher, 2022)
Introduction: Many changes that pregnant women experience affect them from different health perspectives, including quality of life. But many studies report mothers with high social support have better psychological states. This brings about the need for a pregnant woman to have an acceptable form of resilience. Objective: The study aimed to examine selected variables as predictors of perceived social support, quality of life, and resilience in pregnancy. Methods: The study was descriptive and adopted a cross-sectional design. The Multidimensional Scale of Perceived Social Support, Short Form (SF-36) Health Survey 1.0 Questionnaire, and Connor-Davidson Resilience Scale were used for data collection. The population of the study was pregnant women attending antenatal care in the hospital. Systematic sampling was used in selecting the respondents of the study. Data were analyzed using SPSS version 26 and presented as frequencies and percentages, and ordinal logistic regression was used to determine the predictive power of the study's independent variables. Results: Most respondents had poor and very-good perceived social support levels (27.2%), respectively. The majority (76.6%) of the respondents had poor quality of life, and 40.3% had outstanding resilience. Family socioeconomic status was the only variable significantly predicting the levels of perceived social support, P < 0.05. No variable significantly predicted the quality of life and resilience. Recommendation: To boost the social support received by pregnant women and to enhance the quality of life of pregnant women in developing countries, there is a need for the deep involvement of significant people in pregnant mothers' families from conception to delivery